A DISSOLUÇÃO DO VÍNCULO CONJUGAL EM FAMÍLIAS MULTIESPÉCIE: A GUARDA COMPARTILHADA E A RESPONSABILIDADE SOBRE OS ANIMAIS DE ESTIMAÇÃO (REMUNOM, 2024)
This article addresses cases of the dissolution of marital bonds in multispecies families and the resulting consequences for pets. Given the absence of specific legislation on this topic, analogy, customs, and general principles of law are employed to resolve such cases. The article provides a conclusion on how this issue is practically addressed and resolved. The subject is current and highly relevant, as the number of multispecies families in Brazil is growing significantly. Consequently, the number of divorces and dissolutions of stable unions is also increasing. Societal changes have been significant, and the 1988 Federal Constitution expanded the concept of family, prompting the Brazilian legal system to improve in this Regard. The objective of this article is to explain how issues of custody and responsibilities concerning pets in multispecies families are handled, through bibliographic, documentary, and jurisprudential research.